Implementation And Evaluation Of Various Parameters Of Vanet Protocols Using Ns-3 - L.Deepshika Reddy,D.Harika,V.Meghana, Dr. Vyomal N. Pandya, Dr.Y.Sreenivasulu (International Journal of Advanced Science and Technology, 2020)
During the recent decades Vehicular Ad –hoc Networks (VANETs) attract a efficient interest in the research community. VANETs can form links between Vehicle to Vehicle(V2V) and Vehicle to Infrastructure(V2I), so a large no. of applications could be applied. These applications consist safety & entertainment applications that require high availability of the communication system. Let us consider the case of an accident a big amount of messages are being sent into a large scale area. Furthermore the topology is rapidly changing during transmission and automobiles are moving with high velocity. In order to make the communication between automobiles possible, a stable routing protocol is required to ensure that the messages is being transmitted eﬃciently and correctly. So the design of routing protocols is an emergency research area in VANET that have to deal with the problems of frequently changing topology and quick movements ofnodes.